qanda-logo
search-icon
Símbolos
apple-logo
google-play-logo
Problema
solution-image
$x→0$ $1\right)lim\dfrac {\left(x+3\right)^{2}-9} {x}=$ $4\right)lim\dfrac {\left(x+2\right)^{2}-9} {x}=$ $6\right)lim _{\dfrac {x-7} {x2-49}=}$ $x→7$ $x→0$ $h→0$ $2\right)lim\dfrac {\left(2+h\right)^{3}-2^{3}} {h}$ $=$ $5\right)lim\dfrac {x^{2}+x-6} {x^{2}-9}=$ $x→-3$ $7\right)lim\dfrac {x-8} {x^{2-64}}=$ $x→8$ $3\right)lim\dfrac {x^{2}+x-6} {x^{2}-9}=$ $x→-3$ $8\right)lim\dfrac {x^{2}+4x+3} {x^{2}+3x+2}=$ $x→-1$
Bachillerato
Cálculo
Solución
answer-user-profile-image
Profesor de Qanda - aantezana
answer-reply-image
answer-reply-image